Investigating the effects of glucocorticoids and pro-inflammatory cytokines on oxidative stress in the HepG2 cell line - Petersen, Ashlin Veruscka (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.